Do speech–language therapists support young people with communication disability to use social media? A mixed methods study of professional practices - Shelton, Nichola; Munro, Natalie; Keep, Melanie; Starling, Julia; Tieu, Lyn (International journal of language & communication disorders, 2023)
Background Social media is increasingly used by young people, including those with communication disability. To date, though, little is known about how speech–language therapists (SLTs) support the social media use of young people with communication disability. Aims To explore what services SLTs provide to facilitate the social media use of young people with communication disability, including what these services look like, and the factors that impact SLTs’ professional practices. Methods & Procedures A sequential mixed methods approach was employed including an online survey and in‐depth semi‐structured interviews. Participants were qualified practising SLTs in Australia with a caseload that included clients aged 12–16 years. Quantitative data were analysed with SPSS. A thematic analysis of qualitative data was conducted with NVivo. Outcomes & Results Survey responses from 61 SLTs were analysed. Interviews were conducted with 16 participants. Survey data indicated that SLTs do not systematically assess or treat young people's use of social media as part of their professional practice. Interview data revealed that where SLTs do support young people's use of social media, they transfer knowledge and practices typically used in offline contexts to underpin their work supporting clients’ use of social media. In terms of factors that affect SLTs’ practices, three major themes were identified: client/family factors, SLT factors, and societal factors. Conclusions & Implications While young people with communication disability may desire digital participation in social media spaces, SLTs’ current professional practices do not routinely address this need. Professional practice guidelines would support SLTs’ practices in this area. Future research should seek the opinions of young people with communication disability regarding their use of social media, and the role of SLTs in facilitating this. WHAT THIS PAPER ADDS What is already known on the subject Young people with communication disability use social media, but digital inequality means that they may not do so to the same extent as their typically developing peers. Services targeting a young person's social media use is within the SLT scope of practice. Whether or not SLTs routinely address the social media use of young people with communication disability as part of their professional practice is unknown. What this study adds to existing knowledge This study found that SLTs in Australia do not systematically provide professional services targeting young people's use of social media. When services do address a young person's use of social media, knowledge and practices typically used by SLTs in offline contexts are adapted to support their work targeting online social media contexts. What are the potential or actual clinical implications of this work? This study indicates that SLTs should consider a range of factors when deciding whether to address a young person's social media use. Adapting existing offline professional practices to online environments could support SLTs’ work in providing services targeting social media use. Professional practice guidelines would support SLTs’ work facilitating the social media use of young people with communication disability.